2022
DOI: 10.3389/fpsyg.2022.893881
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Motivation to Comply With COVID-19 Protective Measures in Germany

Abstract: The COVID-19 pandemic strains the healthcare systems, economy, education, and social life. Governments took several protective measures and formulated behavioral guidelines to prevent individual diseases and the collapse of healthcare systems. However, individual differences in the extent of compliance with the measures are apparent. To shed more light on this issue, the present correlational study examined the joint relation of several personal characteristics to people's motivation to comply with seven prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…In contrast, self-regulation skills showed no significant association with gender, although female students were found to have higher self-regulation skills in previous works on online learning (Alghamdi et al, 2020 ; Li, 2019 ). A more general explanation for this relation between perceived adaptability and gender could be that female students were more willing to adapt to changing conditions in the context of the Covid-19 pandemic, as also reflected by higher acceptance and compliance with some protective measures (Kaspar & Nordmeyer, 2022 ; Zettler et al, 2022 ). In sum, gender did not play an important role in explaining inter-personal variance in online learning experiences during the Covid-19 pandemic, corroborating previous results (Abdullah et al, 2022 ; Harvey et al, 2017 ; Rizvi et al, 2019 ; Yu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, self-regulation skills showed no significant association with gender, although female students were found to have higher self-regulation skills in previous works on online learning (Alghamdi et al, 2020 ; Li, 2019 ). A more general explanation for this relation between perceived adaptability and gender could be that female students were more willing to adapt to changing conditions in the context of the Covid-19 pandemic, as also reflected by higher acceptance and compliance with some protective measures (Kaspar & Nordmeyer, 2022 ; Zettler et al, 2022 ). In sum, gender did not play an important role in explaining inter-personal variance in online learning experiences during the Covid-19 pandemic, corroborating previous results (Abdullah et al, 2022 ; Harvey et al, 2017 ; Rizvi et al, 2019 ; Yu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…How well students adapt to such life changes can heavily rely on their personal characteristics (Caspi & Moffitt, 1993;Pinquart & Silbereisen, 2004). In line with this theoretical assumption, several studies have found that age, gender, and personality traits are related to how strongly people are worried, perceive risks for their life and society, and accept to follow protective measures to counter the Covid-19 pandemic (Kaspar & Nordmeyer, 2022;Zettler et al, 2022). In fact, 56% of the variance in online learning outcomes at the start of the Covid-19 pandemic could be explained based on university students' personality traits, educational level, and gender (Yu, 2021).…”
mentioning
confidence: 94%
“…It is a reason of concern, however, that a significant proportion of patients did not feel adequately informed about the virus and countermeasures that mitigate virus transmission and dissemination. This in itself is a factor being associated with decreased levels of compliance to official recommendations ( 34 , 37 ). One protective factor could have been here the regular and often daily contact with the OMT clinic, where the SARS-CoV-2/COVID-19 countermeasures were enforced during the pandemic, which may have raised the awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that extraversion, conscientiousness, agreeableness, and openness subscale scores are positively associated with adherence to recommended protective measures. In contrast, Neuroticism is negatively related to these measures (Aschwanden et al, 2021;Kekäläinen et al, 2021;Kaspar and Nordmeyer, 2022;Moore et al, 2022;Otterbring and Festila, 2022). Additionally, previous studies have demonstrated the significant influence of the following personality traits, including aversion to infection (Stangier et al, 2021), self-control (Rodriguez et al, 2023), internal and external locus of control (Krampe et al, 2021), cultural values (Lu et al, 2021), curiosity (Losecaat Vermeer et al, 2022, and optimism (Sheetal et al, 2020) on health-protective behaviors.…”
Section: Role Of Personality Traits During the Covid-19 Pandemicmentioning
confidence: 94%